Acute effect of popular high-intensity functional training exercise on physiologic markers of growth - Kliszczewicz, B.; Markert, C. D.; Bechke, E.; Williamson, C.; Clemons, K. N.; Snarr, R. L.; McKenzie, M. J. (The Journal of Strength and Conditioning Research, 2021)
Constantly evolving, high-intensity functional training (HIFT) exercise consists of various modalities, orders, weights, and repetition schemes. High-intensity functional training has gained popularity among the general population, but lacks empirical evidence regarding acute adaptive responses. The purpose of this study was to describe the acute effects of 2 representative bouts of HIFT on physiologic markers of growth. For convenience, the bouts are designated "short" (<5 minutes) and "long" (~15 minutes), although duration was not the only difference between bouts. Ten apparently healthy men (28.1 ± 5 years) performed 2 HIFT bouts in a randomized crossover design. Blood was collected at 5 time points (Pre, Post, 1, 3, and 6 hours) to examine growth hormone (GH), insulin-like growth factor (IGF-1), insulin-like growth factor binding proteins 1 and 2 (IGFBP-1 and IGFBP-2), and vascular endothelial growth factor (VEGF). Blood lactate concentration ([La]) was analyzed at the Pre and Post time points. A repeated-measures analysis of variance (ANOVA) revealed no trial differences among the markers (IGF-1, IGFBP-1, IGFBP-2, and VEGF) except GH at Post, where the long bout produced a greater effect (p = 0.005). Mean GH levels (pg/ml) in the short bout increased from 68.4 to 106.5, and in the long bout, mean GH levels increased from 38.5 to 286.4. The repeated-measures ANOVA revealed a main time effect in GH (p = 0.037), while a post hoc t-test demonstrated elevated GH at 1 hour (p = 0.018) when compared with Pre. No time-dependent change (p > 0.05) was observed in IGF-1, IGFBP-1, IGFBP-2, or VEGF. Mean blood [lactate] increased more than tenfold in both bouts. The findings of this descriptive study suggest that, other than GH, there are no acute differences in markers of skeletal muscle or vascular growth between these 2 specific HIFT bouts.